Pengaruh Penerapan Teknik Pomodoro Dalam Pembelajaran PPKN Terhadap Peningkatan Konsentrasi Belajar Peserta Didik (Studi Pra-Eksperimen Di Kelas Xi Ipa 1 Sman 8 Kota Serang Tahun Ajaran 2024/2025) - Nur Eva Lestari; Ria Yuni Lestari; Wika Hardika Legiani (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to determine the effect of applying the Pomodoro technique in PPKn (Civics Education) learning on improving students’ learning concentration. The research method used is a quantitative approach with a pre-experimental design, namely the One Group Pre-test Post-test Design, conducted at SMAN 8 Kota Serang. The population in this study consists of students in grade XI of SMAN 8 Kota Serang. The sampling technique used was purposive sampling, with only class XI IPA 1 selected as the experimental class, without the use of a control class. Data collection techniques included questionnaires, observation, and documentation. The data analysis technique used statistical processing, including normality testing and hypothesis testing. The hypothesis testing technique used was the Wilcoxon sign test. The results of the hypothesis test using the Wilcoxon sign test showed an Asymp. Sig (2-tailed) value of 0.000, which is less than 0.05. This indicates that H₀ is rejected and H₁ is accepted. This means that there is a significant difference between the pre-test and post-test results of students’ learning concentration. Therefore, the hypothesis testing demonstrates that the hypothesis is accepted, or in other words, the application of the Pomodoro technique in PPKn learning has an effect on improving the learning concentration of students in class XI IPA 1 SMAN 8 Kota Serang